Socrates the Homer-lover as portrayed in Plato, Xenophon and Aristophanes - Yamagata, Naoko (2022)
Sócrates es retratado como un aficionado de Homero en los diálogos de Platón, tanto explícitamente a través de su expresión de afecto y respeto a Homero desde niño (República 595b9-10), como implícitamente a través de sus numerosas citas y referencias. Del mismo modo, Sócrates utiliza con frecuencia referencias homéricas en los diálogos que Jenofonte escribió para preservar sus recuerdos. El estudio comparativo de estos autores hasta ahora sugiere que el Sócrates histórico se sirvió de Homero con frecuencia en su conversación. Sin embargo, también debería considerarse si ese retrato coincide con el Sócrates representado en las Nubes de Aristófanes, una fuente más contemporánea que las obras de Platón y Jenofonte. Este artículo examina la representación de Sócrates en las Nubes y argumenta que aquí, también, podemos encontrar un reflejo de su afecto a Homero, especialmente en su invocación de las Nubes en las líneas 265-74. También se considerará cómo esa representación de Sócrates puede afectar nuestra visión de Sócrates.
Socrates is portrayed as a Homer-lover in Plato's dialogues, both explicitly through his expression of love and respect for Homer since his childhood (Republic 595b9-10) and implicitly through his numerous Homeric quotations and references. Similarly, Socrates frequently uses Homeric references in the dialogues that Xenophon wrote to preserve his memories. The comparative study of these authors so far suggests that the historical Socrates did use Homer often in his conversation. However, we should also consider whether that portrait matches the Socrates depicted in Aristophanes' Clouds, a more contemporary source than Plato and Xenophon's works. This paper examines the portrayal of Socrates in the Clouds and argues that here, too, we can find a reflection of his love of Homer, especially in his invocation of the Clouds in lines 265-74. It will also consider how that portrayal of Socrates can affect our view of Socrates.
Keywords: Sócrates; Homero; Platón; Jenofonte; Nubes; Socrates; Homer; Plato; Xenophon; Aristophanes; Clouds